The analysis of blood coagulation changes in patients with hypertension in combination with chronic obstructive pulmonary disease varying degrees of severity - Samoilova, Svitlana; Plenova, Olga; Shkala, Lyubov (ScienceRise: Medical Science, 2017)
Aim of research was to determine the influence of COPD severity on the plasma hemostasis condition in patients with HT combined with COPD. Materials and methods. 79 patients were examined: 15 almost healthy (control) and 64 patients with stage II HT with concomitant COPD. Depending on the COPD severity, the patients were divided into 3 groups: group A- 11 patients with HT and COPD of the I severity degree; Group B - 28 patients with HT and COPD of the II severity degree; Group B - 25 patients HT and COPD of the III severity degree. Special laboratory tests: coagulation indicators - activated partial thromboplastin time, prothrombin time, thrombin time, fibrinogen, soluble fibrin monomer complexes, ancistron test, Lebetox test, and echitox test were carried out. Results: in result of the study it was found that comorbid HT and COPD course is characterized by increased activity of hemostasis system coagulation level, which intensity is associated with bronchial obstruction severity. In particular, COPD of the III severity degree hyperfibrinogenemia, as well as soluble fibrin monomer complexes significant increase were observed in all subgroups of the patients with HT and COPD, accompanied by activation of external pathway of coagulation and combined with accelerated processes of prothrombinase-, trombino- and fibrin formation according to specific snake venoms tests. Conclusion. Comorbid HT and COPD course is characterized by the activation of hemostasis system coagulation level, which intensity is associated with bronchial obstruction severity. Hyperfibrinogenemia and a significant increase of the SFMC content, observed in all subgroups of the patients with HT and COPD, at COPD of the III severity degree are accompanied by activation of external pathway of coagulation and combined with accelerated processes of prothrombinase-, trombino- and fibrin formation according to specific snake venoms tests. The patients with HT combined with COPD of the III severity degree need careful laboratory monitoring to solve the problem of the additional antithrombotic correction necessity